1998
DOI: 10.1016/s0010-0277(98)00032-8
|View full text |Cite
|
Sign up to set email alerts
|

Motor processes in mental rotation

Abstract: Much indirect evidence supports the hypothesis that transformations of mental images are at least in part guided by motor processes, even in the case of images of abstract objects rather than of body parts. For example, rotation may be guided by processes that also prime one to see results of a specific motor action. We directly test the hypothesis by means of a dual-task paradigm in which subjects perform the Cooper-Shepard mental rotation task while executing an unseen motor rotation in a given direction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
334
3
8

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 485 publications
(371 citation statements)
references
References 25 publications
19
334
3
8
Order By: Relevance
“…Thus, the execution of rotational hand movements facilitated the simultaneously performed mental rotation when the directions of rotation matched. Wexler, Kosslyn, and Berthoz (1998) provided corroborating evidence. In their study, the participants were asked to mentally rotate two-dimensional geometric figures (used in Cooper & Shepard, 1973) while the hand holding a joystick made rotary movement.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Thus, the execution of rotational hand movements facilitated the simultaneously performed mental rotation when the directions of rotation matched. Wexler, Kosslyn, and Berthoz (1998) provided corroborating evidence. In their study, the participants were asked to mentally rotate two-dimensional geometric figures (used in Cooper & Shepard, 1973) while the hand holding a joystick made rotary movement.…”
mentioning
confidence: 59%
“…The external motor strategy is replaced by more efficient internal strategies. This internalization process can explain Wexler et al's (1998)'s finding that overt rotary movement by the hand facilitated mental rotation performance in the first half but not in the second half of the experiment. The external motor strategy, in the form of spontaneous gestures, thus, gradually becomes more liberated from constraints of the physical world.…”
Section: Deagentivization and Internalization Of The Motor Strategymentioning
confidence: 91%
“…Moreover, the fact that SMA is activated during task responding while more rostral mesial areas are recruited during task processing strengthens Wexler's thesis that mental rotation recruits motor planning and anticipation, but not the cortical and subcortical mechanisms responsible for movement execution (Wexler et al, 1998). It has been speculated that M1 activity, during mental rotation of figures of hands, was caused by the subjects visualizing themselves manipulating their right hands (Parsons et al, 1995;Kosslyn et al, 1998).…”
Section: Discussionmentioning
confidence: 82%
“…Theoretical concepts suggest that dynamic imagery and overt movements rely on the same neural networks, i.e., they are functionally equivalent (Prinz, 1997;Weimer, 1997). In a recent study, Wex-ler et al showed that subjects performing a mental rotation task and an unseen rotation in a given direction exhibited shorter reaction times and fewer errors when the motor rotation direction was compatible with the mental rotation direction (Wexler et al, 1998). The authors concluded that mental rotation would recruit motor planning and anticipation, but not the cortical and subcortical mechanisms responsible for movement execution.…”
Section: Introductionmentioning
confidence: 99%
“…"Dynamic" or "spatial" mental imagery involves spatial relations (e.g., location) and the mental manipulation or transformation of images. This type of mental imagery, which is found in tasks entailing mental rotation or orientation discrimination, is strongly linked to motor processes (Vingerhoets et al, 2002;Wexler et al, 1998c), and seems to depend on the dorsal stream pathway (Farah, 1989;Podzebenko et al, 2002) and on the brain structures underlying the procedural system: Broca's area (Jordan et al, 2001;Podzebenko et al, 2002); premotor regions, including both lateral premotor cortex and the SMA (Cohen et al, 1996; Jordan et al, 2001;Kosslyn et al, 1998;Podzebenko et al, 2002;Richter et al, 2000;Tagaris et al, 1997); the basal ganglia (Podzebenko et al, 2002); the cerebellum (Ivry and Fiez, 2000;Podzebenko et al, 2002); and parietal cortex (Bestmann et al, 2002;Harris et al, 2000;Podzebenko et al, 2002), including the supramarginal gyrus (Harris et al, 2000;Podzebenko et al, 2002). In contrast, "static" or "visual" imagery, which involves imaging static objects or their features (e.g., color, form), is linked to the perception and processing of this type of information, to occipital and temporal regions, and to the ventral stream pathway (which is closely related to declarative memory; see above) (Farah, 1989;Farah, 1995;Goodale, 2000).…”
Section: Mental Imagerymentioning
confidence: 99%